PARALLEL BETWEEN THE REFUGEE CONCEPT ACCORDING TO THE CONVENTION RELATING TO THE STATUS OF REFUGEES FROM 1951 AND ITS PROTOCOL FROM 1967 AND THE REFUGEE CONCEPT ACCORDING TO EUROPEAN LAW - Patricia Casandra PAPUC (Challenges of the Knowledge Society)
In this study our aim is to make a comparison between the refugee concept according to the Convention Relating to the Status of Refugees from 1951 and its Protocol from 1967 which represent the international approach and the refugee concept according to European Law ( the EU Treaties, EU Directives, the Dublin Regulation). This parallel will present first of all the similarities between the international approach and the European approach such as : the definition of a refugee; the conditions required to obtain refugee status; the definition of the term injury; same request for international protection; same parameteres used to verify the existence of persecution; the conditions of cessation and the non refoulement principle. Second of all the we will present the differences between the international approach and the European approach. European law completes the Convention and introduces new principles such as: subsidiary protection; temporary protection; different degrees of protection offered to refugees; the term persectution is defined ; the motivation behind persecution is defined ; recognising as persecution also the acts toward gender and children. Furthermore the cessation clause and the exclusion clause are defined differently in European law in comparison to the definition given by the Convention Relating to the Status of Refugees from 1951 and its Protocol from 1967. Lastly we will conclude with a set of recommendations for both the Convention Relating to the Status of Refugees as well as for the European asylum system.